Foreshadowing and Its Results to Plot Twist in Lloyd F. Loux’s A Clever Catch - Rommel Utungga Pasopati; Laura Ika Angelina Arfina Putri; Sinta Uli Simbolon; Pandu Bagus Sutowijoyo; Yoshua Veron Handika Putra Siadari (Wahana : Tridarma Perguruan Tinggi, 2025)
This article investigates how the plot twist in Lloyd F. Loux’s A Clever Catch is done through foreshadowing. The action of foreshadowing is to introduce subconscious clues to the audience without spoiling the result. Loux’s story is about a man who has an obsession with a thief woman and intends to catch her. At last, he succeeds in catching the thief and brings her before the magistrate, but then the magistrate does not punish her but gives best wishes to both of them. Through qualitative method and explorative approach, this paper underlines that the plot twist is preceded by the senses of law, starting from the thief, the accusation, the man as the detective, and the magistrate. At last, the punishment is not severe, but happy since all of the symbols eventually indicate a man who goes after a woman he loves. In conclusion, the foreshadowing in Loux’s story brings suspense and anxiety to the audience which then later presents a grateful happy ending as the plot twist.